PENGARUH KENAIKAN HARGA BAHAN POKOK TERHADAP KESEJAHTERAAN MASYARAKAT DI KEDUNGWUNI - Retnoria Dwi Lestari (UIN K.H. Abdurrahman Wahid Pekalongan, 2023)
The purpose of this study is to determine the impact of rising prices of basic commodities on the welfare of the people in Kedungwuni. This type of research uses a qualitative descriptive method. The results of this research study are staple foods that make it difficult for people to meet their daily needs. There are many factors that cause this case. The first is the uncertain weather factor, which causes rice field farmers to fail to harvest, and results in reduced distribution to the community. The two factors are the condition of the paddy fields which makes it impossible to plant rice. The third is the agent's delay in sending merchandise so that traders run out of merchandise stock. There are several factors that are the cause of this case. From this case it can lead to a lack of public consumption, because people's income is smaller than the price of basic commodities for consumption which continues to increase and rising prices of basic commodities can result in the welfare of households who previously could meet almost all their needs. In anticipating price increases, especially for basic needs, the government's role is very much needed. The central government and regional governments must focus more on increasing food production. The development of the agricultural sector should also be carried out through an agribusiness approach so that agricultural production has added value and high selling value.